2020
DOI: 10.1111/jch.13960
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal artery ablation for primary aldosteronism without apparent aldosteronoma: An efficacy and safety, proof‐of‐principle trial

Abstract: Primary aldosteronism (PA) is associated with resistant hypertension and cardiovascular events. There are some limitations of current medical and surgical therapies for PA. To determine the efficacy and safety of catheter‐based adrenal artery ablation for treatment of PA patients who refused both surgery and medical therapy, we performed this prospective cohort study. Thirty‐six PA patients without apparent aldosteronoma were treated by adrenal artery ablation. Primary outcome was postoperative blood pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Although laparoscopic adrenalectomy is the standard surgical treatment for APA, various treatments have been developed for reducing invasiveness: minimally invasive partial adrenalectomy [186], robot-assisted partial adrenalectomy [187], radiofrequency ablation for adrenal adenomas [188], and adrenal artery ablation [189], respectively. These new techniques are expected as an alternative treatment when patients have no desire for surgery or under general anesthesia is not indicated.…”
Section: New Interventional Techniquesmentioning
confidence: 99%
“…Although laparoscopic adrenalectomy is the standard surgical treatment for APA, various treatments have been developed for reducing invasiveness: minimally invasive partial adrenalectomy [186], robot-assisted partial adrenalectomy [187], radiofrequency ablation for adrenal adenomas [188], and adrenal artery ablation [189], respectively. These new techniques are expected as an alternative treatment when patients have no desire for surgery or under general anesthesia is not indicated.…”
Section: New Interventional Techniquesmentioning
confidence: 99%
“…AVS was performed in all patients without adrenocorticotropic hormone simulation, and this was performed as described in our previous study [ 18 ]. Sampling was regarded as successful when the selectivity index (SI, defined as cortisol in the adrenal vein/cortisol) was ≥2.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, adrenal venous sampling (AVS) is used as the gold standard for aldosterone lateralization [17]. In our previous study, we also found a 50% inconsistency rate between CT and AVS among 32 cases [18]. Therefore, the aim of our present study was to examine the prevalence of metabolic disorders in different subtypes of patients with PA diagnosed via AVS, as well as to determine whether the presence of MS aggravates the severity of organ damage.…”
Section: Introductionmentioning
confidence: 94%
“…The Chongqing Endocrine Hypertension Collaborative Team conducted several other studies. Zhang et al [12] reported a prospective cohort study of catheter-based adrenal ablation in 36 PA patients without apparent aldosteronoma. Complete and partial clinical success was achieved in 9 (25.0%) and 13 (36.1%) patients, respectively.…”
mentioning
confidence: 99%